Capsaicin responsiveness and cough in asthma and chronic obstructive pulmonary disease. Issue 8 (1st August 2000) - Doherty, M J; Mister, R; Pearson, M G; Calverley, P M A
Abstract : BACKGROUND: Chronic cough is associated with an increased sensitivity to inhaled capsaicin in a number of conditions but there are no data for patients with more severe asthma or chronic obstructive pulmonary disease (COPD). Moreover, the relationships between the capsaicin response (expressed as the concentration of capsaicin provoking five coughs, C5), self-reported cough, and routine medication is not known. METHODS: The cough response to capsaicin in 53 subjects with asthma, 56 subjects with COPD, and 96 healthy individuals was recorded and compared with a number of subjective measures of self-reported cough, measures of airway obstruction, and prescribed medication. In asthmatic subjects the relationships between the cough response to capsaicin and mean daily peak flow variability and non-specific bronchial hyperresponsiveness to histamine were also examined. RESULTS: Subjects with asthma (median C5 = 62 mM) and COPD (median C5 = 31 mM) were similarly sensitive to capsaicin and both were more reactive than normal subjects (median C5 >500 mM). Capsaicin sensitivity was related to symptomatic cough as measured by the diary card score in both asthma and COPD ( r = –0.38 and r = –0.44, respectively), but only in asthma and not COPD when measured using a visual analogue score ( r = –0.32 and r = –0.05, respectively). Capsaicin sensitivity was independent of the degree of airway obstruction and in asthmatics was not related to PEF variability or PC20 for histamine. The response to capsaicin was not related to treatment with inhaled corticosteroids but was increased in those using anticholinergic agents in both conditions. CONCLUSIONS: These data suggest that an increased cough reflex, as measured by capsaicin responsiveness, is an important contributor to the presence of cough in asthma and COPD, rather than cough being simply secondary to excessive airway secretions. The lack of any relationship between capsaicin responsiveness and airflow limitation as measured by the FEV1 suggests that the mechanisms producing cough are likely to be different from those causing airways obstruction, at least in patients with COPD.